Supplementation of Brotowali Stem Meal (Tinospora Crispa L) in the Diet on Performance, and Organ Immunity of Hybrid Ducks Gunsi 888 - M. A. A. A. Nurdin; R. Mutia; W. Hermana (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
The management of microbial infections in poultry farming continues to be largely antibiotic-dependent. Despite this, the application of Antibiotic Growth Promoters (AGPs) in poultry feed has been banned, necessitating the use of herbal feed additives such as Brotowali (Tinospora crispa). This study aimed to evaluate the effects of Brotowali stem meal on the performance and immune organs of hybrid ducks. A total of 200 hybrid ducks Gunsi 888 were used in this study, reared from 11 to 46 days of age. The ducks were fed either a basal diet as a control (P1) or a basal diet supplemented with 0.5% Brotowali stem meal (P2), 1% (P3), and 1.5% (P4). The observed immune organs included the thymus, bursa of Fabricius, and spleen. The study was conducted in Bogor, West Java, while the an analysis of Brotowali’s phytochemical properties was conducted at the Tropical Biopharmaca Research Center of IPB University. All collected data were analyzed using analysis of variance (ANOVA), and significant differences were further analyzed using Duncan’s Multiple Range Test (DMRT) with SPSS version 25. The results showed that Brotowali stem meal had no significant effect (P>0.05) on the immunity of hybrid ducks. However, Brotowali stem meal significantly (P<0.05) improved the performance of hybrid ducks, as evidenced by increased body weight and decreased feed conversion ratios. In conclusion, Brotowali can enhance the performance of hybrid ducks, and it does not affect the stress levels of the livestock.